2000
DOI: 10.1046/j.1365-2036.2000.00726.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and fiscal impact of lansoprazole intolerance in veterans with gastro‐oesophageal reflux disease

Abstract: Background: Omeprazole was replaced by lansoprazole as the only proton pump inhibitor on the Veterans Affairs (VA) formulary in February 1997. We aimed to assess the clinical and fiscal impact of this conversion at two VA hospitals. Methods: We identified lansoprazole intolerant patients using pharmacy databases. We reviewed medical records to obtain data regarding reasons for lansoprazole intolerance. The costs of the formulary change and the savings to the VA were calculated. Results: A total of 3833 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…It has been our anecdotal experience that with each antisecretory drug substitution program performed at our hospital (e.g., cimetidine to ranitidine, ranitidine to nizatidine, omeprazole to lansoprazole [LAN], LAN to rabeprazole [RAB]), some of our patients have complained that the new drug was less effective and have requested to be switched back. This experience is similar to that reported by other hospitals [4][5][6][7]. For example, at the Palo Alto VA hospital, approximately 10% of veterans who were switched from omeprazole to LAN were subsequently switched back.…”
Section: Introductionsupporting
confidence: 82%
See 3 more Smart Citations
“…It has been our anecdotal experience that with each antisecretory drug substitution program performed at our hospital (e.g., cimetidine to ranitidine, ranitidine to nizatidine, omeprazole to lansoprazole [LAN], LAN to rabeprazole [RAB]), some of our patients have complained that the new drug was less effective and have requested to be switched back. This experience is similar to that reported by other hospitals [4][5][6][7]. For example, at the Palo Alto VA hospital, approximately 10% of veterans who were switched from omeprazole to LAN were subsequently switched back.…”
Section: Introductionsupporting
confidence: 82%
“…Twenty-one percent of the patients switched back [5]. Another study examined data obtained at a single time point and found a similar proportion with increased symptoms (29%) but the proportion increased was balanced by those who reported symptom improvement [4,7] with no change in median symptom score. Overall 78% were satisfied or neutral about the exchange.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This has the potential to add further complication because certain PPIs can occasionally cause diarrhea and in rare cases cause colitis. 39,40 …”
Section: Analgesicsmentioning
confidence: 99%